Determinants and variability of river low-flows in selected geographical regions of Poland in the period 1989–2018 - Kozek-Połomska, Malwina; Tomaszewski, Edmund (Acta Geographica Lodziensia, 2024)
The aim of the study was an identification and variability assessment of river low-flows in five big catchments in Poland that, due to their size and location, reflect the predominant features of the physico-geographical regions in which they lie. There were 92 gauging cross-sections with daily discharge series selected in the period 1989–2018. The data were taken from the database of Polish Institute of Meteorology and Water Management – National Research Institute. Low-flows were identified on the base of the Threshold Level Method where truncation discharge corresponded to the 70th percentile on the Flow Duration Curve. During analysis, multiannual and seasonal variability of low-flow duration, streamflow deficit and their derived characteristics were assessed. The research showed the relationship of precipitation distribution and water balance structure with average low-flow duration and the number of identified episodes. Specific features of catchments determining low flows development were indicated. They resulted primarily from features of the catchment hydrogeological and hydrographic structure, land cover and evapotranspiration intensity. Attention was paid to shaping seasonal features of low-flows both in terms of their origin and the dynamics of development. The main anthropogenic factors have been identified which affect the course of low-flows.